If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -5 = x + 3 Reorder the terms: -5 + 7x = x + 3 Reorder the terms: -5 + 7x = 3 + x Solving -5 + 7x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + 7x + -1x = 3 + x + -1x Combine like terms: 7x + -1x = 6x -5 + 6x = 3 + x + -1x Combine like terms: x + -1x = 0 -5 + 6x = 3 + 0 -5 + 6x = 3 Add '5' to each side of the equation. -5 + 5 + 6x = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 6x = 3 + 5 6x = 3 + 5 Combine like terms: 3 + 5 = 8 6x = 8 Divide each side by '6'. x = 1.333333333 Simplifying x = 1.333333333
| 3(x-2)-q=6(x-5) | | 8=v+8+7v | | 8(3+4b)=-168 | | x^2+4x+52=0 | | 3y+10.5=65+2.5y | | t^2+28t+75=0 | | 15+n=21 | | 22-d=38 | | 8(1-5a)=35 | | m/8-1=2 | | .75y-6=.25y+1 | | X=x^3+4x^2-6 | | 5x^2y+3xy^2-5yx^2+3-5y^2x= | | y*5/6=120 | | 7p-(3p+4)=-2(4g+1) | | sN=21 | | m/8–1=2 | | -5+8x=-133 | | 20a-18a=14 | | 4(2x+8)=12x+16 | | 5(y+x)-4(y+3x)= | | 8(2+5r)=-144 | | -25+2=50 | | 5+3(7-x)+6x=-42 | | m^2-34m=0 | | 1/3x3.14x42x42x84 | | 19u-11u-4u=16 | | 1=k/6-3 | | 4/9*m=8/3 | | 8q-1/4q | | k/6-3 | | 18d-17d-d+d=18 |